Looking at Abortion Jurisprudence of the European Court of Human Rights as an Equality Issue - Kaisla Yli-Juuti (Groningen Journal of International Law)
This article explores how, when and to what extent could a finding of a violation of Article 14 ECHR provide substantive benefit to those who have been denied legal abortion in their home States and are seeking justice under the ECHR framework. This topic is extremely relevant as it allows for a critical evaluation of the Court’s approach to equality and abortion judgements from the perspective of substantive equality and feminist legal theory. Access to safe and legal abortion services is an equality question because the ability to control when one has children directly influences how equally one can participate in public life. The Court’s current use of formal equality, based on the idea that those in similar situations should be treated in the same way, makes the application of an equality approach to its abortion cases impossible. It is proposed that the Court should adopt substantive equality instead. This article follows Sandra Fredman’s multidimensional concept of substantive equality composed of the redistributive, recognition, participatory and transformative dimensions. The substantive equality approach recognises that individuals cannot be separated from their characteristics. The aim is to change the underlying structures that cause inequalities in the first place and to celebrate differences instead of fitting everyone into the same box. A finding of a violation of Article 14 ECHR by the Court would provide additional benefits for those seeking justice under the ECHR framework for being denied legal abortions in their home States and would have a substantial impact as it would lead to acknowledging the disadvantages of belonging to certain groups, elimination of harmful gender stereotypes and to possible changes in domestic laws of the Contracting Parties due to the Court’s influence.